Roger Fry et Clive Bell : divergences fondamentales autour de la notion de « Significant Form » - Jutras, Pierrette (RACAR : Revue d'art canadienne / Canadian Art Review, 1993)
The fundamental differences between the formalism of Roger Fry and that of Clive Bell far outweigh the few part of communalities that are often recalled to fuse, and confuse, one with the other. More specifically, the axioms which underwrite their respective views of “significance,” “form,” “significant and expressive form” or “Significant Form,” imply orientations and meanings which are so antithetic that they must be read as opposing rather than supporting each other. Such is the global conclusion resulting from a comparative analysis of texts from both authors written over a period of some twenty-five years (1909-1934). This analysis was conducted around such themes as the relationship of art and life, the means and methods of access to the aesthetic experience, and the manifestations and finalities of those experiences. The findings are fourfold. First, while Fry wants art to serve as a “double life,” unfaillingly rooted in and attentive to the human experience in this world, Bell feels art to be entirely devoted to “another world” and totally independent of—and oblivious to—the human experience. Second, while Fry presumes that anyone willing to work at learning and developing visual and perceptual skills can gain access to the aesthetic experience, Bell declares that only those born with the “aesthetic sensibility” will ever reach its peaks. Third, while Fry’s aesthetic experiences produce a variety of affects of different intensities (feelings or emotions, Bell’s “grand aesthetic thrill” is unique and always possessed of ecstatic intensity. Fourth, while Fry involves art in a process of cognition and communication, Bell glorifies art as a refuge and an escape from all communication and articulated cognition. Obviously, then, the significances and forms envisaged and supported within each of these contexts are irreconcilable.